Trust-Significance, Definitions and Dimensions: A Literature Search - Hasnain, Sheikh Shamim Shamim (Archives of Business Research, 2019)
This is a literature based paper addressing the significance, definitions and dimensions of trust. Trust is a crucial subject matter for many social science disciplines. Researchers could reveal that trust reduces risk, increases productivity, builds a strong relationship between the colleagues in the work place, helps in transferring knowledge between the individuals and organisations, builds team work, minimizes controls, reduces expenditures, reduces competitive attitudes and makes decision making easy. Trust is difficult to define. Researchers and theorists have defined trust in different ways. Trust is defined in numerous ways. Trust dimensions show the various elements and ingredients of trust constituting trust. The definitions and dimensions of trust identified by the researchers are frequently repetitive and concurrent. Future researchers may empirically examine the impact of trust dimension on various issues in the organisations.